What can I do for you? Optimal market segmentation in service markets - Peter-J. Jost; Anna Ressi (Production and Operations Management, 2022)
This paper considers price competition in a market where two firms sell a homogeneous service to a continuum of customers differing with respect to some exogenous characteristic. Our paper's novelty consists of explicitly acknowledging a distinctive property of many services in that firms incur customer-specific service costs after the contract is signed. Hence, not only the customers' willingness-to-pay and as such demand but also the firms' supply are related to customer characteristics. In this paper, we shed light on the implications thereof for optimal pricing and market segmentation strategies in a monopoly as well as a duopoly market. Importantly, we stress the profitability of services by demonstrating that firms in highly competitive industries still earn positive expected profits in~equilibrium.
Keywords: 650; Bertrand paradox; market segmentation; personalized pricing; services